INTRODUCTION OF GENERAL CADASTRE IN AN ADMINISTRATIVE TERRITORY (PANGEEA, 2025)
Introduction of general cadastre in an administrative territory. General cadastre is an indestructible part of the economy, agriculture, construction, systemization and has an important role in the rational use of the land. The progress made in recent years in the field of cadastre require approach of this issue from a modern perspective of structuring information in accordance with the methods and apparatus used, the ultimate goal being the realization of general cadastre work of Romania.
Keywords: general cadastre; administrative territory; ownership; Land Registry; cadastral plan